2022
DOI: 10.1021/acsabm.2c00149
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Anticancer and Genotoxicity Profiles of Green Synthesized and Chemically Synthesized Silver Nanoparticles

Abstract: Silver nanoparticles were green synthesized (Ag-PTs) employing the crude extract of Padina tetrastromatica, a marine alga, and their anticancer and safety profile were compared with those of chemically synthesized silver nanoparticles (Ag-NPs) by in vitro and in vivo models. Ag-PT exhibited potent cytotoxicity against B16-F10 (IC50 = 3.29), MCF-7 (IC50 = 4.36), HEPG2 (IC50 =3.89), and HeLa (IC50 = 4.97) cancer cell lines, whereas they exhibited lower toxicity on normal CHO-K1 cells (IC50 = 5.16). The potent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Similarly, Rashidipour & Heydari [ 53 ] conveyed that olive leaf Ag-NPs were safe for normal cell lines. Besides, the green synthesis of Ag-NPs revealed less genotoxicity than the chemically produced Ag-NPs [ 65 ]. However, this is the first study to examine the cytotoxic effect of encapsulated olive leaf extract.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Rashidipour & Heydari [ 53 ] conveyed that olive leaf Ag-NPs were safe for normal cell lines. Besides, the green synthesis of Ag-NPs revealed less genotoxicity than the chemically produced Ag-NPs [ 65 ]. However, this is the first study to examine the cytotoxic effect of encapsulated olive leaf extract.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that these extracts induced significant effects in vitro on different cancer lines, from breast cancer, colorectal cancer, bladder cancer, and prostate cancer, to leukemia [77][78][79][80][81]. Even the green synthesized AgNps demonstrated effectiveness in inhibiting cancer cell growth [63,82] and in inducing apoptosis in leukemia cells [83], and that the size and shape of AgNPs play a crucial role in exerting their biological activities on cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“… 21 24 These applications exploit AgNPs’ excellent optoelectronic properties, such as surface plasmon resonance (SPR), small size, high surface-to-volume ratio, and cost effectiveness. 25 , 26 Furthermore, nanosilver is comparatively less reactive than silver ions and is suitable for clinical and therapeutic applications. 27 , 28 AgNPs exhibit a broad spectrum of antibacterial and antifungal properties, depending on their shape, size, and surface chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Current approaches to prevent biofilm formation include modification of surface topography and surface coatings that detain the cells from sticking to a surface. However, these are temporary treatments because most coatings are quickly covered with self-produced ECM polymers, shielding the antifouling coating and allowing the bacterial cells to stick to the surface, despite the coating. Another method related to biofilm eradication includes the use of biocidal molecules, such as silver nanoparticles (AgNPs). , AgNPs comprise one of the most predominant nanomaterials in various products, such as fabrics, bandages, deodorizers, food containers, and disinfectants. AgNPs are also incorporated into hydrogels, creating hybrid antibacterial wound dressings. These applications exploit AgNPs’ excellent optoelectronic properties, such as surface plasmon resonance (SPR), small size, high surface-to-volume ratio, and cost effectiveness. , Furthermore, nanosilver is comparatively less reactive than silver ions and is suitable for clinical and therapeutic applications. , AgNPs exhibit a broad spectrum of antibacterial and antifungal properties, depending on their shape, size, and surface chemistry. The antibacterial activity of AgNPs is related with the release of Ag + ions that may lead to the formation of radical species, which damage cells to a lethal extent …”
Section: Introductionmentioning
confidence: 99%